EGFR targeted albumin nanoparticles of oleanolic acid: In silico screening of nanocarrier, cytotoxicity and pharmacokinetics for lung cancer therapy - Shukla V.N.; Vikas; Mehata A.K.; Setia A.; Kumari P.; Mahto S.K.; Muthu M.S.; Mishra S.K. (My University, 2025)
This study aimed to develop cetuximab (CTX) functionalized albumin nanoparticles (ALB-NPs) of oleanolic acid for EGFR targeted lung cancer therapy. The molecular docking methodology has been applied for a selection of suitable nanocarrier. Various physicochemical parameters like particle size, polydispersity, zeta potential, morphology, entrapment efficiency, and in-vitro drug release of all the ALB-NPs were analyzed. Furthermore, the in-vitro qualitative and quantitative cellular uptake study revealed that higher uptake of CTX conjugated ALB-NPs than nontargeted ALB-NPs in A549 cells. The in-vitro MTT assay revealed that the IC50 value of CTX-OLA-ALB-NPs (4.34 ± 1.90 μg/mL) was significantly reduced (p < 0.001) than OLA-ALB-NPs (13.87 ± 1.28 μg/mL) in A-549 cells. CTX-OLA-ALB-NPs caused apoptosis in A-549 cells at concentrations equivalent to its IC50 value and blocked the cell cycle in the G0/G1 phases. The hemocompatibility, histopathology and lung safety study confirmed the biocompatibility of the developed NPs. In vivo ultrasound and photoacoustic imaging confirmed the targeted delivery of the NPs to lung cancer. The findings demonstrated that CTX-OLA-ALB-NPs have potential for site-specific delivery of OLA for effective and targeted therapy of lung carcinoma. © 2023 Elsevier B.V.